Risk factors of Multidrug Resistant Tuberculosis in central Nepal: A pilot study - Marahatta, S B; Kaewkungwal, J; Ramasoota, P; Singhasivanon, P (Kathmandu University Medical Journal, 2012)
Introduction Tuberculosis is the most widespread infectious disease in Nepal and poses a serious threat to the health and development of the country. Incidences of drug resistant tuberculosis in Nepal are increasing and this tuberculosisis a major threat to successfully controlling tuberculosis . Objective The general objective of the study was to assess the risk factors of multi-drug resistant tuberculosis among the patients attending the National Tuberculosis Centre, Bhaktpur Nepal. Methods An observational study/ case-control study with a Atotal number of 55 multi-drug resistant tuberculosis cases and 55 controls. The study was conducted among the patient attending in the National Tuberculosis Centre , Bhaktpur Nepal for six months, between May–October 2010. sImulti-drug resistant tuberculosis wasThe collected data was analysed in SPSS 11.5 version. The association between categorical variables were analysed by chi-square tests, OR and their 95% CI were measured. Results The total number of patients used for the study was 110, of which among them 55 were cases and 55 were controls . Our study revealed that there were significant associations between history of prior TB MDR-TB OR =2.799 (95 % CI 1.159 to 6.667) (p=0.020); smoking habit OR =2.350 and (95%CI 1.071 to 5.159) (p=0.032); social stigma social stigma OR 2.655 (95%CI r 1.071 to 5.159) (p=0.013); knowledge on MDR-TB OR =9.643 (95% CI 3.339 to 27.846) (p < 0.001)and knowledge on DOTS Plus OR=16.714 (95% CI is ranging from 4.656 to 60.008) (p< 0.001). However, there was no association found between alcohol drinking habits and ventilation in the room. Conclusion Our study revealed that there were significant associations between history of prior tuberculosis, smoking habit social stigma social stigma, knowledge on multi-drug resistant tuberculosis and knowledge on DOTS Plus with multi-drug resistant tuberculosis However there was no association between alcohol drinking habit and ventilation in room with multi-drug resistant tuberculosis. http://dx.doi.org/10.3126/kumj.v8i4.6238 Kathmandu Univ Med J 2010;8(4):392-7